VD_FINDINFO HC / 2009 / 170 vom 5. Juni 2009 - VD Tribunal cantonal (2009)
ASSASSINAT, DÉTRESSE PROFONDE, ERREUR SUR LES FAITSDROIT PÉNAL | 112 CP, 13 al. 1 CP, 47 CP, 48 ch. 2 CP, 48 CP, 54 CP, 415 CPP